Digital personalized medical insole process - Völz Diana; Schneider Julia; Wuttke Ulrich (Current Directions in Biomedical Engineering, 2023)
Medical insoles are used to correct patient’s foot malpositions or to relieve certain foot areas from pressure. The required insole type depends largely on the presenting clinical picture and the individual’s needs. Accurate fit of medical insoles is critical to wearer acceptance, which is a necessary precondition where further serious injury is to be prevented. An end-to-end digital process offers the potential to better adapt insoles to the personalized patients’ foot geometry and pressure load. Furthermore, the whole gait-cycle could be included in the digitalization process and the adaption could consider special needs of different gait phases. This hasn’t been done, yet. For this purpose, a digital process chain was developed and prototypically tested in collaboration with an orthopaedist. 3D scans of the foot geometry in various loaded conditions were compiled and the corresponding gait analysis images were mapped. Both results were overlaid in a CAD program to create a model and identify the clinical picture. Adapted to the geometry of the foot, a volumetric model of the medical insole was built, individual stress zones were separated and filled with lattice structures of different parameters. The insole was 3D printed. The results of the present examination show benefits in using the loaded foot scan to model insoles, as malpositions can be checked automatically via standard (digital) tests. While it is possible to model and print medical insoles in one piece with differing strengths, there is limited information about the influence of the designed lattice structure on a specific printing result (i. e. the material behaviour).